2015
DOI: 10.1175/jpo-d-14-0110.1
|View full text |Cite
|
Sign up to set email alerts
|

Mixing Variability in the Southern Ocean

Abstract: A key remaining challenge in oceanography is the understanding and parameterization of small-scale mixing. Evidence suggests that topographic features play a significant role in enhancing mixing in the Southern Ocean. This study uses 914 high-resolution hydrographic profiles from novel EM-APEX profiling floats to investigate turbulent mixing north of the Kerguelen Plateau, a major topographic feature in the Southern Ocean. A shear-strain finescale parameterization is applied to estimate diapycnal diffusivity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
72
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(77 citation statements)
references
References 105 publications
5
72
0
Order By: Relevance
“…The objective of SOFine was to investigate the relation between finescale processes and the momentum balance in the Antarctic Circumpolar Current (Naveira Garabato 2009; Waterman et al 2013;Damerell et al 2013;Waterman et al 2014;Phillips and Bindoff 2014;Meyer et al 2015;Forryan et al 2015). In this study, the analysis of the internal wave field is based primarily on data from eight EM-APEX Argo-equivalent floats.…”
Section: ) Surveymentioning
confidence: 99%
See 3 more Smart Citations
“…The objective of SOFine was to investigate the relation between finescale processes and the momentum balance in the Antarctic Circumpolar Current (Naveira Garabato 2009; Waterman et al 2013;Damerell et al 2013;Waterman et al 2014;Phillips and Bindoff 2014;Meyer et al 2015;Forryan et al 2015). In this study, the analysis of the internal wave field is based primarily on data from eight EM-APEX Argo-equivalent floats.…”
Section: ) Surveymentioning
confidence: 99%
“…Fronts can be identified using hydrographic criteria such as velocity maxima location, water-mass distribution, and locations where certain hydrographic properties cross particular depths (Belkin and Gordon 1996). Using surface velocity maxima determined from satGEM (Meijers et al 2011), a weekly geostrophic velocity product, Meyer et al (2015) found a coherent and intense jet north of the Kerguelen Plateau over the sampling period of the EM-APEX floats (18 November 2008 to 30 January 2009). The jet was identified as the middle and northern branches of the Subantarctic Front, likely merged with the southern branch of the Subtropical Front.…”
Section: B Regional Oceanographymentioning
confidence: 99%
See 2 more Smart Citations
“…Calibration and quality control of the velocity data are described in Phillips and Bindoff (2014). Quality control of the temperature and salinity dataset is described in Meyer et al (2015).…”
mentioning
confidence: 99%